Evolution of Glacial and High-Altitude Lakes in the Sikkim, Eastern Himalaya Over the Past Four Decades (1975–2017) - Shukla, Aparna; Garg, Purushottam K.; Srivastava, Smriti (Frontiers in Environmental Science, 2018)
Global climate change is significantly triggering the dynamic evolution of high-mountain lakes which may pose a serious threat to downstream areas, warranting their systematic and regular monitoring. This study presents the first temporal inventory of glacial and high-altitude lakes in the Sikkim, Eastern Himalaya for four points in time i.e., 1975, 1991, 2000 and 2017 using Hexagon, TM, ETM+ and OLI images, respectively. First, a baseline data was generated for the year 2000 and then the multi-temporal lake changes were assessed. The annual mapping of SGLs was also performed for four consecutive years (2014-2017) to analyze their nature and occurrence pattern. The results show an existence of 463 glacial and high-altitude lakes (>0.003 km2) in 2000 which were grouped into four classes: supraglacial (SGL; 50) pro/peri glacial lake in contact with glacier (PGLC; 35), pro/peri glacial lake away from glacier (PGLA; 112) and other lakes (OL; 266). The mean size of lakes is 0.06 km2 and about 87% lakes have area < 0.1 km2. The number of lakes increased (by 9%) from 425 in 1975 to 466 in 2017, accompanied by a rapid areal expansion from 25.17 ±1.90 km2 to 31.24 ±2.36 km2 (24%). The maximum expansion in number (106%) and area (138%) was observed in SGLs, followed by PGLCs (number: 34%; area: 90%). Contrarily no significant change was found in other lakes. The annual SGL mapping reveals that their number (area) increased from 81 (543153 m2) to 96 (840973 m2) between 2014 and 2017. Occurrence pattern of SGLs shows that maximum number of lakes (> 80%) are persistent in nature, followed by drain-out (15-20%) and recurring type lakes (7-8%). The new-formed lakes (9-17%) were consistently noticed in all the years (2014-2017). The results of this study underline that regional climate is accelerating the cryosphere thawing and if the current trend continues, further glacier melting will likely occur. Therefore, formation of new lakes and expansion of existing lakes is expected in the study area leading to increase in potential of glacial lake outburst floods. Thereby, persistent attention should be paid to the influences of climatic change in the region.